Insomnia in Elderly : A Review - Rouf, M A (Journal of Brahmanbaria Medical College, 2026)
Background: Insomnia is sleep disorder in which its have trouble falling asleep, staying asleep or waking up too early-addresssed problems of elderly / ageing. Studies indicate that up to 50% of older adults struggle with falling or staying asleep. Various sleep problems in the elderly are linked to *Age-related cognitive decline and normal aging processes can be further disrupted by sleep disturbances caused by medical or psychiatric conditions such as *Chronic pain, depression and dementia. Additionally primary sleep disorders like *Sleep-disordered breathing and periodic limb movements during sleep *Can worsen the situation, especially when combined with other risk factors. Since sleep plays a crucial role in protecting the body and maintaining overall well-being, addressing sleep disorders is essential for a better quality of life. This review focuses on evaluating sleep disorders in elderly / ageing. Methodology: This current study is a systematic review to published studies and articles by using PubMed and Google. Search strategy using appropriate key words and title. Conclusion: Normal elderly / ageing accompanied by changes in the sleep quality, quantity and architecture. Specially there appears to be a measurable decrease in the ability to initiate and maintain sleep accompanied by a decrease in the proportion of the deeper more restorative slow wave sleep and REM sleep in the healthy elderly / ageing. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 39-44